Black ops - Griffin, W. E. B. (New York : Jove Books, 2010)
This is the last of the Presidential Agent series which began with the story of the hijacked airliner. The plot pulls together all the seemingly unconnected threads of the other stories and explains the various characters and their relationships. Griffin is teaching us more Russian history, including the current Russian leadership about which he has strong opinions.
Keywords: Secret service -- United States -- Fiction; Murder -- Fiction; Spy stories